Cause of death eaudiobook - Cornwell, Patricia (Kay Scarpetta, 2007)
It's New Year's Eve, the final night of Virginia's bloodiest year since the Civil War, and another poor soul has turned up dead. Ted Eddings, a scuba diver and investigative reporter who was a favorite at the Medical Examiner's Office, is found thirty feet below the Elizabeth River's icy surface. Kay Scarpetta, Chief Medical Examiner for the state of Virginia, can't help but wonder why she received a phone call from someone reporting the death before the police were notified. Was Eddings probing the frigid depths of the Inactive Ship Yard for a story or simply diving for sunken trinkets? With the advent of a second murder - this one hitting even closer to home - the case envelops Scarpetta, her niece Lucy, and Police Captain Pete Marino in a world where both cutting-edge technology and old-fashioned detective work are critical offensive weapons. Together, they follow the trail of violence to its forbidding and unexpected source.